Isolasi Senyawa Anti Bakteri Geraniol Dari Minyak Sereh Wangi (Citronella Oil) Dengan Menggunakan Distilasi Vakum - Uswatun Hasanah; Zulkifli Zulkifli; Teuku Rihayat; Andi Wardana; Cut Nazia N (Jurnal Teknologi, 2021)
This study aims to increase geraniol levels in citronella oil, using vacuum distillation. Geraniol is a compound that has been legalized by IFRA (Fragrance International Association) as a scent compound, so geraniol is a reference to be formulated in the form of Anti-bacterial perfume products, but the levels of geraniol in citronella oil are still very low. This encourages the processing of fragrant citronella oil to be processed, by increasing geraniol levels using vacuum distillation, with variations in pressure: 8,6,4,2,1 mbar, during operating times: 20, 40, and 60 minutes up to FBP ( Final Boiling Point). Samples were analyzed using GC-MS (Gas Chromatography-Mass Spectrometry), FT-IR, refractive index, and bacterial testing. The results showed that the use of low pressure affected increasing geraniol levels. The maximum increase in geraniol content was 80.11% at a pressure of 1 mbar at the Final Boiling Point operation, with a refractive index of 1.501, whereas in the FTIR test there was an intense broad peak in the range 2200-3200 cm-1 especially at 3086.98cm-1 according to the OH hydroxyl polymer group at Geraniol. This study increased geraniol levels from 20.32% to 80.11%.